Decoupling of labour productivity growth from median wage growth in Central and Eastern Europe - Joris Schröder (The Vienna Institute for International Economic Studies (wiiw), 2020)
The US-centred debate on the decoupling of productivity from workers' compensation has given rise to the question whether this decoupling has also taken place in other countries, and if so, to what degree. However, in-depth analyses of the extent and the underlying causes of wage-productivity decoupling within Europe are still sparse. This is particularly the case for the Central and East European members of the EU (EU-CEE11), where trickle down of increased labour productivity to local workers in the form of compensation and wage growth has been questioned. Existing analyses provide little explanation as to why the gains in productivity are (not) fully passed on in the form of higher compensation, and why this is more pronounced in some countries than in others. This study thus provides an overview of the extent and underlying factors of wageproductivity decoupling with a focus on the EU-CEE11 countries. In general, the results reveal strong crosscountry variation in the amount and underlying reasons for decoupling. Further, we find that the extent of decoupling within the EU-CEE11 is strongly related to the industry structures of these countries, as it is mostly a phenomenon which occurs in countries that have followed an export- and manufacturing-focused development path, while other countries have experienced "reverse decoupling". We provide further insights into this finding by contrasting productivity and compensation developments in industry and construction with those in the service sector and by looking at each EU-CEE11 country individually.
Keywords: E24; J3; D3; J24; 330; labour productivity; compensation; wages; economic growth; wage inequality; labour share